Storytelling and decentralization of identity in the digital environment - Ustyantsev, Nikita Glebovich (Известия Саратовского университета. Новая серия: Серия Философия. Психология. Педагогика, 2022)
This article is devoted to the consideration of such a sphere of modern reality as the representation of a person in the digital environment through the statement. The study analyzes the process, mechanisms and ways of representation through storytelling. The historical aspect appears as an integral part of the exposure of the individual's attitude to the inner and surrounding reality, which is transmitted not only in the form of a refl exive monologue, but also in the form of an installation, an opinion, and a look. The author notes the multi-level use of storytelling in the context of social space and in building digital identity. The work defi nes the philosophical and methodological foundations of the study, describes in detail the provisions of fragmentation and plurality of digital identity. The content of the article indicates the forms of development of storytelling as a communication technology, substantiates the main forms of infl uence on the formation of identity and its broadcasting in the digital surroundings. The article shows how transmedia and cross-platform play the role of connective tissue for overcoming the fragmentation of transmitted meanings. Thus, the consistency in the formation of a single image is maintained. It also takes into account the problem of technological alienation and the ways to overcome it, one of which is storytelling. The involvement of this communication technology and self-presentation appears to be an essential element for the socio-cultural analysis of digital reality and the development of a new problem fi eld associated with the significance of the digital history of the individual.